Structured Reduced Graphene Oxide/Polymer Composites for Ultra-Efficient Electromagnetic Interference Shielding - Yan, Ding-Xiang; Pang, Huan; Li, Bo; Vajtai, Robert; Xu, Ling; Ren, Peng-Gang; Wang, Jian-Hua; Li, Zhong-Ming (Advanced functional materials, 2015)
A high‐performance electromagnetic interference shielding composite based on reduced graphene oxide (rGO) and polystyrene (PS) is realized via high‐pressure solid‐phase compression molding. Superior shielding effectiveness of 45.1 dB, the highest value among rGO based polymer composite, is achieved with only 3.47 vol% rGO loading owning to multi‐facet segregated architecture with rGO selectively located on the boundaries among PS multi‐facets. This special architecture not only provides many interfaces to absorb the electromagnetic waves, but also dramatically reduces the loading of rGO by confining the rGO at the interfaces. Moreover, the mechanical strength of the segregated composite is dramatically enhanced using high pressure at 350 MPa, overcoming the major disadvantage of the composite made by conventional‐pressure (5 MPa). The composite prepared by the higher pressure shows 94% and 40% increment in compressive strength and compressive modulus, respectively. These results demonstrate a promising method to fabricate an economical, robust, and highly efficient EMI shielding material. The rGO/PS composite with segregated architecture is realized via high‐pressure solid‐phase compression molding for efficient EMI shielding. The highest EMI SE of 45.1 dB among rGO based polymer composites is achieved with only 3.47 vol% rGO loading. The high‐pressure molded composite shows 94% and 40% enhancement in compressive strength and modulus compared to conventional‐pressure molded composite.